دور التخطيط الاستراتيجي في إدارة الأزمات (: دراسة حالة وزارة المالية - ولاية النيل الأبيض،2022 - د. وليد برير عيسى (White Nile Journal for Studies and Research, 2024)
The study addressed the role of strategic planning in crisis management. The problem of the study is summarized in the following main question: What is the role of strategic planning in crisis management? The study aimed to identify the importance of planning in crisis management and to know the requirements for successful strategic planning for crisis management. The study assumed that: There is a statistically significant relationship between the requirements for successful strategic planning and crisis management. There is a statistically significant relationship between the obstacles to the success of strategic planning and crisis management. The study used the descriptive method, the deductive method, the inductive method to test the hypotheses, and the analytical method to analyze the data, The study reached several results, including: The study made clear that the requirements for the success of strategic planning for crisis management in the Ministry of Finance are represented by the continuous evaluation of the strategic plans to confront the crisis, cooperation between all parties concerned with the crisis, continuous follow-up of the implementation of the plan to confront the crisis, and precise definition of the strategic objectives. The obstacles to success are Strategic planning in crisis management in the Ministry of Finance is represented by the lack of financial resources to confront crises, the failure to properly monitor the current situation of the crisis, the lack of experience in the field of strategic planning, the lack of flexibility in confronting crises, and the lack of an efficient system that provides accurate data and information about the extent of crises and those affected by them.. The study reached several recommendations, including: working to activate effective means and methods of communication between employees and senior management, because of its role in containing the crisis and dealing with it quickly, working to involve all employees in the ministry in strategic planning, because of its role in being aware of all dimensions and circumstances. The work environment in the ministry.